Mental Guidance in Improving Life Skills for School Dropout Teens at PSBR Yogyakarta - Adiansyah Adiansyah (Counselle| Journal of Islamic Guidance and Counseling, 2022)
Adolescence is the transition of children to adulthood. The transition from the period of children to adulthood triggers many problems faced by adolescents. Therefore, adolescents need education as a basis for meeting the needs needed in order to respond and respond to problems as well as a basis in character formation. But in certain conditions teenagers are faced with educational problems that have taken root, namely the problem of dropping out of school. This is where the role of the government provides solutions and provides alternatives for teenagers who experience dropouts. Adolescent dropouts are given guidance and coaching through non-formal educational institutions or social institutions, one of which is in PSBR Yogyakarta. PSBR is one of the UPT that has the task and function of providing coaching for teenagers out of school. The coaching is done by providing various guidance, one of which is mental guidance and training in various skills needed for teenagers to drop out of school in order to have life skills . This research aims to explore the problems of adolescents dropping out of school and find out the pattern of mental guidance provided by PSBR in order to improve the life skills of adolescents out of school with a qualitative research approach. The study findings found that adolescents who drop out of school have difficulty in adjusting, health problems, religious problems, problems playing a role in society and problems of leisure. Efforts to improve the life skills of teenage dropouts are done through mental guidance and skill guidance.